Prevalence of celiac disease among school-age children in Çorum, Turkey - Atakan Comba,; Nadiye Barış Eren,; Emre Demir, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Celiac disease (CD) is an autoimmune enteropathy that develops in individuals with genetic susceptibility as a result of a permanent sensitivity to gluten found in grains. The prevalence of CD in Turkey is between 0.3% and 1%. However, the prevalence of CD in Çorum, a city in middle Anatolia in Turkey, is unknown. The purpose of this study was to identify the prevalence of childhood CD in Çorum and to detect patients with silent and atypical CD. Materials and Methods: The sample size was calculated using a stratified sampling method, to provide the sample number that would best represent this population. Screenings were conducted using rapid tissue transglutaminase IgA test kits. Results: A total of 1730 students were included in the study; 877 (50.6%) were female. Of students in the city center, 301 (34%) were in primary school, 299 (34%) were in secondary school, and 283 (32%) were in high school. As for towns, 847 (49%) students from 92 schools were included in the study. Eight children had positive screening results; 4 (50%) were female, and the average age was 11.6±3.4 (9-17) years. According to the celiac serology results and endoscopic duodenum biopsies, all children with positive screening results were diagnosed with CD. The prevalence of CD was found to be 0.46% in schoolchildren. Conclusion: Various studies in Turkey have reported a prevalence of CD between 0.6% and 0.9%, with 0.47% reported in a multicenter study. The present study identified CD prevalence as 0.46% (1 in 216) among children in Çorum, Turkey. Cite this article as: Comba A, Barış Eren N, Demir E. Prevalence of celiac disease among school-age children in Çorum, Turkey.Turk J Gastroenterol 2018; 29: 595-600.